The Impact of Autonomous Driving Technologies on Road Safety and Traffic Management (International Journal of Scientific Research and Management (IJSRM), 2024)
Autonomous driving technologies represent a paradigm shift in road transportation, promising to revolutionize road safety and traffic management. This paper explores the multifaceted impact of autonomous vehicles (AVs) on these critical aspects of transportation. Firstly, it examines the potential of AVs to mitigate human error, a leading cause of accidents, through advanced sensing, computing, and decision-making capabilities. Secondly, the paper analyzes the implications of AVs on traffic flow efficiency, including reduced congestion and optimized route planning. Moreover, it investigates the regulatory and infrastructural challenges that must be addressed to facilitate widespread AV adoption. Finally, the study discusses societal considerations such as ethical dilemmas and the socio-economic impacts of AV deployment. By synthesizing current research and projections, this paper aims to provide a comprehensive overview of how autonomous driving technologies can fundamentally transform road safety and traffic management in the near future.